Citokines, Receptors and The Host-Parasite Interaction - Cruz Cubas, Antonio (2000)
This article presents first, a brief overview of some of the main parasitisms that affect the health of million people around the world. Both, the pro tozoosis and the helmintiasis are analyzed from a clinical and epidemiological viewpoint. Next, discussing the interactions between the human immune system and the parasite, we distinguished these into 2 types: those favorable to the parasite survival and those that can kill it. We remembered that in the host-parasite interaction, there is a genetic background which can determine some degrees of host susceptibility and because that the current "genome" programs carry a great importance for the control of these diseases.